2015
DOI: 10.1177/1548512915612601
|View full text |Cite
|
Sign up to set email alerts
|

Modeling, validation and firing-on-the-move control of armored vehicles using active front-wheel steering

Abstract: It is a well-known fact that an armored vehicle will lose its directional stability when firing a large-caliber gun while moving. The instability is caused by the impulse force from firing, acting at the center of a weapons platform that produces a yaw moment at the center of gravity of the armored vehicle. In order to improve the stability, this paper introduces a firing-on-the-move technology for armored vehicles using an active front-wheel steering (AFS) system. The AFS system is proposed to maintain the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…M z is the tire alignment moment from Pacejka's Magic tire model. The detailed derivation and validation of the steering model can be obtained from Aparow et al 17 The validation of armored vehicle is shown in the work by Kadir et al 18 …”
Section: Ride Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…M z is the tire alignment moment from Pacejka's Magic tire model. The detailed derivation and validation of the steering model can be obtained from Aparow et al 17 The validation of armored vehicle is shown in the work by Kadir et al 18 …”
Section: Ride Modelmentioning
confidence: 99%
“…The simulation was performed for a period range of 5-10 s using Runge-Kutta solver with a fixed step size of 0.001 s. The numerical values of the 17-DOF wheeled armored vehicle model parameters are set based on Kadir et al, 18 while the gun model parameters are based on 75 mm KwK 42 caliber size 7 as shown in Table 3.…”
Section: Simulation Parametersmentioning
confidence: 99%
See 1 more Smart Citation